SUPER EDGE MAGIC TOTAL LABELING ON UNICYCLIC GRAPHS - Sepang, Adidarma; Wibowo, P. Anton; Herawati, Bong Bong; Sugeng, Kiki A (Makara Journal of Science, 2018)
Let G = (V,E) be a simple, connected and undirected graph with v vertices and e edges. An edge magic total labeling is a bijection f from V∪E to a set of integers {1,2,…,v+e} such that if xy is an edge of G then the weight of edge f(x)+f(y)+f(xy) = k, for some integer constant k. A super edge magic total labeling is an edge magic total labeling f which f(V) = {1, · · · , v}. In this paper we construct new super edge magic total labeling of special classes of unicyclic that we construct from a super edge magic total labeling of odd cycles. Our construction uses embedding process of odd cycles, which is labeled by edge magic total labeling to grid, and uses edge transformation to obtain interesting new classes of super edge magic total unicyclic graphs.